France's International Strategy on Gender Equality in France - Athirha, Widhia Andhini Nur; Anggraini, Yayuk (Research Horizon, 2024)
This study aims to investigate France's contribution to promoting gender equality through the implementation of France's International Strategy on Gender Equality (2018-2022) policy in the world of work. The research method used is descriptive. The data sources used are books, journals, and news that can be accounted for, as well as official statistical data from news portals and government agencies. The analysis technique used is secondary analysis, with a qualitative approach to explain French policies in supporting gender equality. Interviews, focus group discussions, web-based research, and document and archive studies were used to collect and analyze relevant data. The results of this study reveal that France has adopted a series of laws to promote gender equality in the workplace since the early 20th century. The French government responded to public demands through various demonstrations, including the #MeToo movement and Gender Equality demonstrations, and took concrete steps through France's International Strategy on Gender Equality.